Identification of three phase generic load model parameters using field measurements - Gul, O. (IEEE, 2004)
This paper presents a new time domain load modeling technique based on the method of instantaneous symmetrical components (ISC) for three-phase unbalanced and distorted power system loads. ISC is used here to obtain instantaneous symmetrical voltage and current components and these components are used in the calculation of the symmetrical component model parameters, resistance, inductance, capacitance and a harmonic instantaneous current source, which are all connected in parallel.